Mycotoxins in raw materials, beverages and supplements of botanicals: A review of occurrence, risk assessment and analytical methodologies. (July 2022) - Pallarés, N.; Tolosa, J.; Ferrer, E.; Berrada, H.
Abstract: Over recent years, consumer interest in natural products, such as botanicals has increased considerably. One of the factors affecting their quality is the presence of mycotoxins. This review focuses on exploring the mycotoxin occurrence in botanicals (raw material and ready-to-eat forms such as infusions or tablets) and the risk assessment due to their ingestion. Aflatoxins, Ochratoxin A, and Fumonisins are the most commonly studied mycotoxins and data in the literature report levels ranging from traces to 1000 μg/kg in raw materials. In general, the highest contents observed in raw materials decreased to unconcerning levels after the preparation of the infusions, reaching values that generally do not exceed 100 μg/L. Regarding botanical dietary supplements, the levels observed were lower than those reported for other matrices, although higher levels (of up to 1000 μg/kg) have been reported in some cases. Risk assessment studies in botanicals revealed a higher risk when they are consumed as tablets compared to infusions. Analytical methodologies implied in mycotoxin determination have also been contemplated. In this sense, liquid chromatography coupled to fluorescence detection has been the most frequently employed analytical technique, although in recent years tandem mass spectrometry has been widely used.